ANALISIS STRUKTUR KOMUNIKASI ORGANISASI DALAM MENINGKATKAN KINERJA KARYAWAN PT SIMATELEX DI KOTA BATAM - tampubolon, yuli; Rorong, Michael Jibrael (SCIENTIA JOURNAL, 2023)
Organisational communication between leaders and subordinates is very important to know because from a good communication, a good relationship between leaders and subordinates is established. From the results of observations, it was found that the common problems experienced by a company are disharmonious relationships between superiors and subordinates, this is due to the lack of trust of superiors to subordinates or vice versa, policy making without transparency, and lack of communication and others. This company experiences various obstacles in its operations caused by obstacles in the communication process, causing a decrease in employee performance. This research was conducted to find out the communication pattern in PT Simatelex Batam City, for the interaction process of PT Simatelex in building relationships and to find out the organisation's strategy in improving employee performance The type of research used is qualitative research. The subjects of this research are Production Leader, Production Line Leader and Production Operator. The results showed that the communication patterns that are often used at PT Simatelex are Circle Pattern, Wheel Pattern, Y Pattern and Star Pattern. Furthermore, the interaction process that exists at PT simatelex, especially the production department, to build relationships between companies and employees, namely with personal relationships and simatelex strategies in improving employee performance, namely time and facilities.